LEKSIKON SERAPAN BAHASA INGGRIS KE DALAM BAHASA MANDARIN TINJAUAN FONOLOGI DAN SEMANTIK - Yanti Bestari, Elsa Astrida; Urip, Sri Rejeki; Sari, Titin Komala (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2018)
Abstract___________________________________________________________________The use of a foreign language, especialy English which isabsorbed into Chinese, can enrich the lexicons of Chinese. In this paper, the writer used descriptive qualitative method. In collecting the data, the writer used a library research method. The data was then analyzed by using a descriptive qualitative method. From the phonological point of view, the absorption of English into Chinese can be categorized into nine sound changes: (1) vocal change, (2) vocal addition, (3) vocal removal, (4) consonant change, (5) consonant addition, (6) consonant removal, (7) syllable addition, (8) syllable removal, (9) loan-translation. From the semantics point of view, the absorption can be categorized into three changes: (1) extending the meaning, (2) narrowing the meaning, (3) completely changing the meaning. The study analyzed there are 164 English vocabularies which is absorbed into Chinese, among 149 vocabulariesare sound changes, and 15 vocabularies are translating. From that vocabularies there are 24 vocabularies are meaning changes, among 9 vocabularies are extending the meaning, 8 vocabularies are narrowing the meaning, and 7 vocabularies are completely changing the meaningAbstrak__________________________________________________________________Penyerapan kosakata dari bahasa asing khususnya bahasa Inggris ke dalam bahasa Mandarin dapat memperkaya leksikon atau perbendaharaan kata bahasa Mandarin.Penelitian ini merupakan penelitian deskriptif kualitatif.Dalam pengumpulan data digunakan teknik studi pustaka dan dalam analisis data digunakan metode deskriptif kualitatif. Dari sudut pandang fonologi, penyerapan terbagi ke dalam beberapa jenis proses perubahan: (1) perubahan vokal, (2) penambahan vokal, (3) penanggalan vokal, (4) perubahan konsonan, (5) penambahan konsonan, (6) penanggalan konsonan, (7) penambahan suku kata, (8) penanggalan suku kata, (9) penterjemahan. Kemudian dari sudut pandang semantik penyerapan kata asing mengalami perubahan makna yang terbagi ke dalam tiga kategori: (1) meluas, (2) menyempit, (3) perubahan total. Berdasarkan hasil penelitianterdapat 164 kosakata serapan bahasa Inggris ke dalam bahasa Mandarin, di antaranya 149 kosakata mengalami perubahan bunyi, dan 15 kosakata mengalami penyerapan penterjemahan. Dari kosakata serapan tersebut terdapat 24 kosakata mengalami perubahan makna, di antaranya 9 kosakata mengalami perluasan mkana, 8 kosakata mengalami penyempitan makna, dan 7 kosakata mengalami perubahan makna total.